Temperature dependent effect of difenoconazole on enzymatic activity from the soil - Filimon Marioara Nicoleta; Voia Sorin Octavian; Vladoiu Diana Larisa; Isvoran Adriana; Ostafe Vasile (Journal of the Serbian Chemical Society, 2015)
The purpose of this study was to quantify the effect of difenoconazole (DFC) on the activity of a few enzymes commonly found on soil: dehydrogenase, urease, phosphatase and protease. Three experimental variants were established: in field conditions with variable temperature (10-21 °C, variants A1-A3), under laboratory conditions with constant temperature (30 °C, variants B1-B3) and untreated soil (C variant). The commercial product "Score 250EC" with 250 g DFC L-1 was used at the following concentrations: 0.037 mg DFC g-1 soil (variants A1 and B1), 0.075 mg DFC g-1 soil (variants A2 and B2) and 0.150 mg DFC g-1 soil (variants A3 and B3). The dehydrogenase, phosphatase and urease activities decreased significantly (p<0.05) both under filed (variants A1-A3) and laboratory (variants B1-B3) conditions compared to untreated soil (variant C). The protease activity was reduced in variants A1-A3 compared to variant C and increased at the dose of 0.150 mg DFC g-1 soil in the variant B3.